Research on the temperature and humidity distribution characteristics in potato storage facilities: experimental analysis and numerical simulation - Zhen, Qi; Xu, Chao; Tana,; Wang, Hongzhi; Yue, Xinwei; Yan, Caixia; Sun, Yunfeng (Frontiers in Sustainable Food Systems, 2025)
Potatoes rank among the world’s most important food crops. Traditional storage methods often lack precise environmental control, rendering potatoes vulnerable to rot and spoilage. Scientific storage, which entails accurate regulation of temperature and humidity, is critical for maintaining potato quality during storage. In this study, the focus is on advancing the scientific storage of potatoes. An experimental platform for potato storage was developed, and experiments were conducted to regulate temperature and humidity within the storage environment. A numerical simulation model of the platform was established based on computational fluid dynamics (CFD). The accuracy of the numerical model was validated by comparing with the experimental results. Furthermore, the airflow, temperature, and humidity distribution within the storage environment were analyzed under varying air supply velocities, temperatures, and humidity levels. Based on the storage characteristics of potatoes and practical experience, the optimal conditions for regulating the temperature and humidity in the potato storage environment on this platform are an air supply temperature of 3°C, an air supply velocity of 5 m/s, and an air supply humidity of 90%.